Collective bargaining for self-employed workers in Europe approaches to reconcile competition law and labour rights - Waas, Bernd; Hiessl, Christina; Hendrickx, Frank; Blanpain, R. (Roger) 1932-2016; Countouris, Nicola 1975- (Bulletin of comparative labour relations, 2021)
'Collective Bargaining for Self-Employed Workers in Europe' gives an up-to-date analysis and discussion on the law and practice of collective bargaining by and for the self-employed in Europe. The increase in the number of self-employed workers has raised the spectre of horizontal price-fixing by self-employed members of a profession. With a view to the increasing prevalence of self-employed work characterized by a manifest imbalance of bargaining power between the contracting parties, there is a vital need to overcome these obstacles to exercise an internationally recognized fundamental labour right. It is now commonplace for companies to offer various forms of non-standard employment that shift risk from the labour engager to the labour provider - which may increase the likelihood of those workers to fall outside the legal concept of 'employee'. The book combines an analysis of the supranational framework by experts in labour law as well as competition law with in-depth country reports from Member States of the EU that have regulation or practices of collective bargaining for the self-employed in place.